Pemberdayaan nelayan berbasis pendidikan ekonomi dan potensi pesisir di Kabupaten Minahasa Utara - Edwin Wantah (Universitas Negeri Malang, 2017)
This research article aims to analyze the needs of traditional coastal fishermen empowerment in North Minahasa Regency North Sulawesi Province based on economic education and coastal potential. This research uses descriptive qualitative research design using survey method, field observation, interview and Focus Group Discussion. Research subjects are coastal fishermen of Minahasa Utara amounting to 40 fishermen spread in 3 sub-districts of East Likupang Subdistrict, Kema District and Wori Sub-district of North Minahasa Regency which has capture capacity of 5 Gross Ton downward. The results of the needs analysis are identified in the observation, in-depth interviews and the Focus group Discussion which confirmed by the survey results showed that 85% of fishermen need knowledge and understanding of the characteristics, attitudes and principles to become successful entrepreneurs who can be implemented in productive activities in the coastal, 90% require knowledge of business diversification based on coastal and marine potentials (fishermen alternative business), 90% stated that they need knowledge and understanding of processing of fish processing products as coastal and marine potential, because of abundant raw materials, 80% requiring literacy on how to build business partnerships and business networks with other business groups, 90% stated that they need literacy on establishing a joint venture group of fishermen and how to develop the business group. 92, 5% Fishermen need literacy on venture capital and access to venture capital and 85% say they are in need of money management, planning for proper financial allocations and saving procedures KeywordsNeeds Analysis, Fishermen Empowerment, Economic Education, Coastal Potential. http://dx.doi.org/10.17977/um022v2i22017p095